2022
DOI: 10.1530/eje-21-0510
|View full text |Cite
|
Sign up to set email alerts
|

S-GRAS score for prognostic classification of adrenocortical carcinoma: an international, multicenter ENSAT study

Abstract: Objective Adrenocortical carcinoma (ACC) has an aggressive but variable clinical course. Prognostic stratification based on the European Network for the Study of Adrenal Tumours stage and Ki67 index is limited. We aimed to demonstrate the prognostic role of a points-based score (S-GRAS) in a large cohort of patients with ACC. Design This is a multicentre, retrospective study on ACC patients who underwent adrenalectomy. Methods The S-GRAS score was calculated as a sum of the following points: tumour stage (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 43 publications
0
46
0
Order By: Relevance
“…The recently validated S-GRAS (Stage, Grade based on the Ki67 labeling index, Resection status and Symptoms) scoring scheme has shown a better prognostic significance compared to the tumor stage and Ki67 proliferation index in patients with adrenal cortical carcinomas [ 169 ]. The Ki67 proliferation index is a component of the Helsinki scoring system that uses the proliferation index as a continuous numeric value [ 132 ].…”
Section: Question 9: What Is the Role Of Mitotic Tumor Grade And The ...mentioning
confidence: 99%
“…The recently validated S-GRAS (Stage, Grade based on the Ki67 labeling index, Resection status and Symptoms) scoring scheme has shown a better prognostic significance compared to the tumor stage and Ki67 proliferation index in patients with adrenal cortical carcinomas [ 169 ]. The Ki67 proliferation index is a component of the Helsinki scoring system that uses the proliferation index as a continuous numeric value [ 132 ].…”
Section: Question 9: What Is the Role Of Mitotic Tumor Grade And The ...mentioning
confidence: 99%
“…The other forecasting methodology is the GRAS parameter, which includes the grade (Ki67 index), resection status, age, and symptoms caused by tumors or hormone secretion. The recently proposed S-GRAS score system combines the GRAS parameter and ENSAT stage ( 9 ), where the latter is a classical method for predicting the prognosis of ACC, although it was not confirmed as an independent predictor in several cohorts ( 17 , 18 ). Ki67 and the resection status have been consistently recognized as factors with significant prognostic power in most studies, although an interobserver variation of Ki67 was found in previous studies ( 9 , 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Survival data, causes of death, and postoperative treatment were collected through outpatient clinical visits or by telephone. The S-GRAS score was calculated as a sum of the following points: tumor stage (1–2 = 0; 3 = 1; 4 = 2), grade (Ki67 index 0–9% = 0; 10–19% = 1; ≥20% = 2 points), resection status (R0 = 0; RX = 1; R1 = 2; R2 = 3), age (<50 years = 0; ≥50 years = 1), symptoms (no = 0; yes = 1), and categorization, which generated four groups (0–1, 2–3, 4–5, and 6–9) ( 9 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The disease stage according to modified European Network for the Study of Adrenal Tumors (mENSAT) classification, 26 tumor Grade, Resection status, Age of patients and presence of Symptoms at ACC diagnosis (accordigly to the GRAS parameters), 27 , 28 resection status of the primary tumor, and previous ACC-correlated medical and surgical treatments were collected.…”
Section: Methodsmentioning
confidence: 99%